Strategi Peningkatan Kinerja Rantai Pasok Keripik Singkong (Studi Kasus di UD Bima Jember) - Siti Nuraini; Ati Kusmiati; Ratih Apri Utami; Cindera Rosa Damascena (Jurnal Agribisnis Indonesia, 2026)
UD Bima is a small–medium cassava chips enterprise in Jember Regency that continues to face several operational challenges, including fluctuating raw-material availability, limited labor capacity, and unsystematic production documentation. This study aims to evaluate the operational performance of UD Bima through the assessment of key performance indicators in planning, procurement, and distribution activities. The SCOR model is employed as a framework for structuring performance indicators, while the Analytical Hierarchy Process (AHP) is used to determine the priority weights of the indicators. Performance achievement is assessed using Snorm de Boer normalization and the Traffic Light System. Bima’s operational activities, and data were collected through interviews, observation, and documentation. This research adopts a descriptive-analytical method, with data collected through interviews, observations, and documentation studies.  The results show an overall operational performance score of 77.63 (good), supported by relatively stable performance in raw material procurement, production processes, and customer complaint handling.  However, several critical indicators—such as production planning, delivery timeliness, record-keeping, and financial documentation—remain in the red category and require immediate improvement. These findings indicate that imrovements in planning systems, operational information management, and internal coordination are necessary to support the sustainability of UD Bima’s operations.